Competitive Intelligence : Gathering, Analysing and Putting it to Work. - Murphy, Christopher (Ashgate Pub., 2007)
Every business manager needs intelligence to find suppliers, mobilize capital, win customers and fend off rivals. Drawn from the author?s own experiences and from a wide variety of disciplines, Competitive Intelligence provides a readable, practical and i.